An Islamic Law-Based Curriculum Model for Islamic Religious Education: Promoting the Development of Law-Abiding Character - Muhammad Faisal Azmi; Andi Khadafi; Ismail Ismail; Sulaiman Sulaiman; A. Muthallib (LOCUS MEDIA PUBLISHING, 2026)
This study examines the development of an Islamic law-based curriculum model in Islamic Religious Education as an effort to strengthen students’ law-abiding character in contemporary educational settings. The research addresses the growing concern over moral degradation, disciplinary violations, and weak legal awareness among students, which indicate the need for a more integrative educational approach grounded in Islamic values and legal principles. The purpose of this study is to formulate a curriculum model that integrates the principles of Islamic law into learning objectives, instructional materials, teaching strategies, and character assessment. This study employs a qualitative approach using literature review and conceptual analysis of Islamic educational theories, curriculum studies, and Islamic legal sources. The findings reveal that the integration of Islamic legal values within Islamic Religious Education contributes significantly to the development of students’ discipline, responsibility, justice, obedience to rules, and social ethics. Furthermore, the proposed curriculum model encourages the internalization of legal consciousness through contextual and value-oriented learning processes. Therefore, the curriculum model is expected to serve as an alternative framework for strengthening character education in Islamic educational institutions.